2022
DOI: 10.1590/1984-0462/2022/40/2020388
|View full text |Cite
|
Sign up to set email alerts
|

Early neonatal sepsis: prevalence, complications and outcomes in newborns with 35 weeks of gestational age or more

Abstract: Objective: To analyze the incidence, complications, and hospital discharge status in newborns with ≥35 weeks of gestational age with early neonatal sepsis. Methods: This is a cross-sectional, retrospective study. Cases of early-onset sepsis registered from January 2016 to December 2019 in neonates with gestational age of 35 weeks or more were reviewed in a level III neonatal unit. The diagnoses were performed based on the criteria by the Brazilian Health Regulatory Agency (Anvisa), and the episodes were class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…This manuscript was published in 2000, and this result, at that time, motivated the present study's team to proceed with conservative management and to value the clinical manifestations of the disease, despite the presence of risk factors for EOS. 13 In the neonatal unit of the present study, the overall prevalence of EOS in NB ≥ 35 weeks evaluated in another evaluation was also low - a rate of 4/1000 living births and that of proven EOS was 0.3/1000 live births, 14 as in a more recent North American study. 3 …”
Section: Discussionsupporting
confidence: 58%
“…This manuscript was published in 2000, and this result, at that time, motivated the present study's team to proceed with conservative management and to value the clinical manifestations of the disease, despite the presence of risk factors for EOS. 13 In the neonatal unit of the present study, the overall prevalence of EOS in NB ≥ 35 weeks evaluated in another evaluation was also low - a rate of 4/1000 living births and that of proven EOS was 0.3/1000 live births, 14 as in a more recent North American study. 3 …”
Section: Discussionsupporting
confidence: 58%
“…A study in Brazil reported EOS rates comparable to HICs at 4.0/1000 live births and confirmed EOS at 0.31/1000 live births, 45 although the sample size was limited to n=46, and the authors acknowledged that all neonates enrolled to the study were >35 weeks gestational age; a distinction many studies do not make in their analysis. Lower figures were however also reported by Freitas and Romero (2017), with an EOS incidence in Brazil of 1.7/1000 live births, 46 and a recent publication from Suriname reported a similar EOS incidence rate of 1.37/1000 live births, for data collected between 2017–2018.…”
Section: Epidemiology Of Eos In Lmics In South Americamentioning
confidence: 99%
“…Clinically presented with fever, hypothermia, difficulty breathing, lethargy, poor feeding, poor neonatal reflexes, abdominal distention, vomiting diarrhea, tachycardia, bradycardia, increased capillary refill time, signs of decreased perfusions, seizures, obtundation, oliguria, renal and liver failure etc. [14] Sepsis is further classified into early onset neonatal sepsis that occurs within 48 hrs to 7 days, late onset neonatal sepsis occur from 7 to 28 days the most common organisms are staphylococcal aureus and e coli, kleibseilla, pseudomonas, salmonella and GBS [15] [16].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The incidence load of newborn sepsis is more in developing countries and where regular surveillance is not observed. Globally sepsis accounts for 27.5% of neonatal deaths [15]. Globally NNS occurs in 1 to 50 per 1000 live births resulting in 3% to 30% of neonatal deaths annually.…”
Section: Literature Reviewmentioning
confidence: 99%